2000
DOI: 10.4049/jimmunol.165.11.6015
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: STAT6-Deficient Mice Have Enhanced Tumor Immunity to Primary and Metastatic Mammary Carcinoma

Abstract: STAT4 and STAT6 are essential for the development of CD4+ Th1 and Th2 development, respectively. Tumor immunologists have hypothesized that Th1 cells are critical in tumor immunity because they facilitate differentiation of CD8+ T cells, which are potent anti-tumor effectors. We have used STAT4−/− and STAT6−/− mice to test this hypothesis. BALB/c and knockout mice were challenged in the mammary gland with the highly malignant and spontaneously metastatic BALB/c-derived 4T1 mammary carcinoma. Primary tumor grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 25 publications
(12 reference statements)
7
80
1
Order By: Relevance
“…It has been hypothesized that the development of Th1 cells optimizes CD8-mediated tumor immunity (7), and hence STAT6 Ϫ/Ϫ mice were thought to be more tumor resistant because they predominantly make Th1 cells. In vivo depletion studies in the mammary carcinoma system, however, contradicted this hypothesis and demonstrated that although CD8 ϩ T cells are essential for tumor rejection by STAT6 Ϫ/Ϫ mice, CD4 ϩ T cells are not involved (3). In contrast, depletion of CD4 ϩ cells increases immunity in the fibrosarcoma system; however, additional studies suggest that the enhancement is due to depletion of regulatory CD4 ϩ NKT cells, rather than CD4 ϩ Th cells (1).…”
Section: Ice With a Deleted Stat6 Gene (Stat6 ϫ/ϫ Mice)mentioning
confidence: 73%
See 3 more Smart Citations
“…It has been hypothesized that the development of Th1 cells optimizes CD8-mediated tumor immunity (7), and hence STAT6 Ϫ/Ϫ mice were thought to be more tumor resistant because they predominantly make Th1 cells. In vivo depletion studies in the mammary carcinoma system, however, contradicted this hypothesis and demonstrated that although CD8 ϩ T cells are essential for tumor rejection by STAT6 Ϫ/Ϫ mice, CD4 ϩ T cells are not involved (3). In contrast, depletion of CD4 ϩ cells increases immunity in the fibrosarcoma system; however, additional studies suggest that the enhancement is due to depletion of regulatory CD4 ϩ NKT cells, rather than CD4 ϩ Th cells (1).…”
Section: Ice With a Deleted Stat6 Gene (Stat6 ϫ/ϫ Mice)mentioning
confidence: 73%
“…As an alternative explanation to Th1 vs Th2 CD4 ϩ helper cell ratio, it has been proposed that STAT6-deficient mice have enhanced immunity because they lack an inhibitor that blocks the development of tumor-reactive CD8 ϩ T cells (1,3). In the primary fibrosarcoma system, IL-13 produced by CD4 ϩ NKT cells has been hypothesized as the inhibitor (1).…”
Section: Ice With a Deleted Stat6 Gene (Stat6 ϫ/ϫ Mice)mentioning
confidence: 99%
See 2 more Smart Citations
“…40). Previous studies implicated STAT6 as possible factor involved in immune suppression associated with myeloid cells (14,41,42). We have demonstrated important role of STAT3 in accumulation of Gr-1 ϩ IMC in cancer (13), and a number of groups demonstrated important role of STAT1 in regulation of iNOS activity (43,44).…”
Section: Figurementioning
confidence: 99%